A cost utility analysis on weaning patients with short bowel off parenteral nutrition following restoration of bowel continuity. (June 2017) - Adaba, F.; Webb, T.; Iqbal, F.; Eastwood, J.; Gabe, S.M.; Tan, E.; Vaizey, C.J.; Nightingale, J.M.D.; Warusavitarne, J.
Summary: Introduction: Home parenteral nutrition (HPN) is an expensive therapy. Restoring bowel continuity has been shown to wean patients off HPN. The aims of this study were to estimate the economic impact and QALY gained after restoring bowel continuity in adult patients with short bowel and intestinal failure due to mesenteric infarction. Method: A Markov cohort model was constructed to simulate patients undergoing bowel restoration following mesenteric infarction. Probabilities associated with restoration of bowel continuity were determined using published data. Costs were estimated using the National Health Service (NHS) reference costs (2013–14). Utilities were determined from literature and opinion of experts. Results: The expected QALY at 1 year following restoring bowel was 0.47. This increased to 3.29 at 5 years. The marginal cost per QALY gained calculated for the first year following restoration of bowel continuity was £95959.72 and this decreases to £10797.63 at 5 years. Conclusion: Restoring bowel continuity reduces the overall costs associated with HPN and it results in increased QALY over time.